An Enlightening commentary into the light of The Holy Qur'an - Ayatullah Sayyid Kamal Faghih Imani (Amirul Mu'minin Ali AS Liberary, 2004)
ws. jl.1,2,4,5-6,9,10,12,13.c.1-2, jl.3,11 .c.1 Jl.7,c.1-3, jl.8.c.1-4